Green synthesis of CuO nanoparticles from Cucurbita maxima leaf extract; a platinum free counter electrode for dye sensitized solar cells - Emma Panzi Mukhokosi; Stephen Tenywa; Nandipha L. Bothab; Shohreh Azizi; Mathapelo Pearl Seopela; Malik Maaza (Journal of Nigerian Society of Physical Sciences)
Green synthesis of metal oxides has attracted attention as the latest technology in synthesizing metal oxide nanoparticles due to its simplicity, cheapness, non-toxicity and its ability for large scale production. Metal oxides find applications in dye sensitized solar cells (DSSCs) as counter electrodes (CEs) and photo-anodes. However, applications of green synthesized metal oxides as counter electrodes have not been fully explored. In this study, CuO nanoparticles (NPs) were synthesized from Cucurbita maxima leaf extract and applied as a CE in DSSC. Uniformly synthesized CuO NPs were subjected to various characterization tools to obtain the crystal structure, surface morphology, particle size, optical properties, chemical bonds and photovoltaic properties. Using a natural dye from of Cucurbita maxima as a photon absorber, a short circuit current density ( Jsc) of 4.2 µA/cm2, open circuit voltage (Voc) of 0.17 V, a maximum power (Pmax) of 0.18 mW/cm2, and a power conversion efficiency (PCE) of 1.8 × 10?4 % under one-sun illumination were obtained.